P15.04.B Serial18F-fluciclovine PET-CT and multiparametric MRI during chemoradiation for glioblastoma - an exploratory clinical study with pre-clinical correlation. (5th September 2022) - Fatania, K; Fernandez, S; Shaw, G C; Salvatore, D; Teh, I; Schneider, J E; Murray, L; Scarsbrook, A F; Short, S C; Currie, S
Abstract: Background: Positron emission tomography (PET) using anti-1-amino-3- 18 fluorine-fluorocyclobutane-1-carboxylic acid ( 18 F-fluciclovine) shows preferential glioma cell uptake with low activity in normal brain. Dynamic contrast-enhanced (DCE) MRI may also be used to investigate regions of glioma that do not show gadolinium-enhancement on post-contrast T1-weighted MR sequences (Gd-T1) and may reflect tumour infiltration beyond the Gd-T1 enhancing margin. There is a paucity of data on how 18 F-fluciclovine uptake correlates with Gd-T1 and DCE-MRI activity, how it correlates with tumour biology and whether significant changes in uptake occur during treatment. The aims of this pilot study were: 1 To compare 18 F-fluciclovine PET, DCE-MRI and Gd-T1 in patients undergoing chemoradiotherapy for glioblastoma (GBM) 2 To investigate correlation between 18 F-fluciclovine uptake, MRI findings, and tumour biology in a pre-clinical glioma model. Material and Methods: 18 F-fluciclovine-PET-CT and MRI including DCE-MRI were acquired before, during and after adjuvant chemoradiotherapy (60 Gy in 30 fractions with temozolomide) in GBM patients. DCE-MRI and Gd-T1 volumes were manually contoured, and PET volumes defined using semi-automatic thresholding. Gd-T1 was subtracted from PET and DCE-MRI volumes to identify areas beyond the Gd-T1 volume boundary and similarity of the PET and DCE-MRI volumes outside the Gd-T1 volume boundary were measured using the Dice similarity coefficient (DSC). CT-2A tumour cells were stereotactically injected into the right striatum of 8 to 10-week-old C57BL6J mice and they underwent MRI and 18 F-fluciclovine PET-CT. Post-mortem mice brains underwent immunohistochemistry staining for ASCT2 (amino acid transporter), nestin (stemness) and Ki-67 (proliferation) to assess for biologically active tumour. Results: 6 patients were recruited (GBM 1-6). For GBM 1-3: PET volumes were greater than DCE-MRI, in turn greater than Gd-T1. For GBM 4-6, Gd-T1 volumes were similar to DCE-MRI and both were greater than PET volumes. GBM 1-3 had lower overall survival than GBM 4-6: median 249 vs. 903 days. 18 F-fluciclovine uptake and Gd uptake (on DCE-MRI) was seen beyond the margins of the standard Gd-T1 volume. Comparing these regions beyond the Gd-T1 margins, the PET and DCE-MRI had low DSC, suggesting distinct areas of fluciclovine and DCE-MRI uptake. Pre-clinical PET-CT demonstrated tumour-specific 18 F-fluciclovine uptake which corresponded to biologically active tumour based on immunostaining for Ki-67, nestin and ASCT2. Conclusion: Results from this joint pre-clinical and clinical pilot study suggest volumes of 18 F-fluciclovine-PET activity beyond that depicted by MRI-DCE and Gd-T1 are associated with a poorer prognosis in patients undergoing chemoradiotherapy for GBM. The pre-clinical model confirmed 18 F-fluciclovine uptake reflected biologically active tumour.